Pengawasan Pusat terhadap Daerah (Kajian terhadap Peraturan Daerah "Bermasalah") - Ni'matul Huda (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The annulment of district regulation by the Minister of Home Affairs is the form of repressive controlling for the region should be taken after decision of The Supreme Court who cancelled the district regulation. To minimize the deviation in making district regulation, it would be better that the government have a guidance for the local regulation especially for making district regulation and the decision of region in chief continuously. Endorsed Laws or Decision of District in chief returned after revising immediately, so that the possible mistakes on drafting the district regulation or the Creed could be minimized as soonas possible.